2019
DOI: 10.1007/s13199-019-00628-0
|View full text |Cite
|
Sign up to set email alerts
|

Do silver nanoparticles stimulate the formation of ectomycorrhizae in seedlings of pedunculate oak (Quercus robur L.)?

Abstract: Metal nanoparticles are gaining ever-wider application in agriculture and forestry, as alternatives to chemical agents used as fertilisers, growth stimulators and pesticides, establishing a need for eco-toxicological risk assessment of these agents. We tested the effects of foliar-applied silver nanoparticles (AgNPs) on chlorophyll a fluorescence and on abundance and species composition of ectomycorrhizal (ECM) colonisation. The application of AgNPs at concentrations of 5, 25 and 50 ppm was found to stimulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…167 Likewise, Ag NPs (20.4 ± 3.2 nm) caused similar effects, generating plant growth inhibition and decreased root mycorrhizal colonization rate. 168 However, recent studies showed beneficial effects: Ag NPs (5 nm mean size) stimulated the formation of mycorrhizae in seedlings of pedunculate oak (Quercus robur L.), 169 and biologically synthesized TiO 2 NPs (68 nm mean size) enhanced root colonization of common bean (Phaseolus vulgaris L.) with the arbuscular mycorrhizal fungi (Funneliformis mosseae) and improved salinity tolerance compared to inoculation with arbuscular mycorrhizal fungi alone. 170 These seemingly contradictory results expose the complexity of the relations involved and highlight the necessity to consider every experimental parameterin particular, precise optimization of doses and modes of application.…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…167 Likewise, Ag NPs (20.4 ± 3.2 nm) caused similar effects, generating plant growth inhibition and decreased root mycorrhizal colonization rate. 168 However, recent studies showed beneficial effects: Ag NPs (5 nm mean size) stimulated the formation of mycorrhizae in seedlings of pedunculate oak (Quercus robur L.), 169 and biologically synthesized TiO 2 NPs (68 nm mean size) enhanced root colonization of common bean (Phaseolus vulgaris L.) with the arbuscular mycorrhizal fungi (Funneliformis mosseae) and improved salinity tolerance compared to inoculation with arbuscular mycorrhizal fungi alone. 170 These seemingly contradictory results expose the complexity of the relations involved and highlight the necessity to consider every experimental parameterin particular, precise optimization of doses and modes of application.…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
“…170 These seemingly contradictory results expose the complexity of the relations involved and highlight the necessity to consider every experimental parameterin particular, precise optimization of doses and modes of application. 169,170…”
Section: Effects Of Nanoparticles In Soil and Soil Microbiotamentioning
confidence: 99%
“…Research is underway to develop NPs that can improve the nutrient and pesticide delivery to plants [ 4 ]. NPs are used in agriculture as nano-fertilizers to increase plant growth, as pesticides to manage the harmful effects caused by pests on the crop, and sometimes also as sensors to monitor the soil quality and plant health [ 5 ]. The extensive use of NPs in various fields raises the concern that they are released into the environment and interact with the plant through their shoot part or root part positively or negatively [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%